Sistem Informasi Pelajar Sains Komputer (SIPSKom) - Nor Azlina, Aziz Fadzilah (2002)

(untitled)
The study attempt to produce a prototype courseware for computer science subject ITC 120 Object Oriented Computer Programming Language. The system provides an interactive learning and teaching environment for lecturers and students. The Object Modeling Technique (OMT) is the system methodology used in the study. Student Information System (SIPKom) consists of five modules : information, student, lecturer, course and programs. This study is presented in a web-based environment. All students and lecturers can upload this subject online which will be connecting as a local area network (LAN) basis.